Top-Down Budgeting-An Instrument to Strengthen Budget Management - Ljungman, Gosta (IMF Working Papers; Working Paper ;, 2009)
This paper examines the rationale for a top-down approach to budget preparation and approval, and discusses some factors that have to be considered when reorienting the budget process along these lines. The paper argues that the sequence in which budgetary decisions are taken matters, and that a strong top-down approach strengthens fiscal discipline and improves policy prioritization and coordination. Top-down budgeting also alters the division of roles and responsibilities between the central budget authority and line ministries, and requires that the process of determining the total expenditure level, sectoral allocations and individual appropriations is clarified. Finally, the paper argues that strong top-down elements in the parliamentary budget voting process can be effective in addressing the risk of excessive and unsustainable amendments during budget approval.